Winter distribution and size structure of Antarctic krill Euphausia superba populations in-shore along the West Antarctic Peninsula - Cleary, Alison C; Durbin, Edward G; Casas, Maria C; Zhou, Meng (Marine Ecology Progress Series, 2016)
Antarctic krill Euphausia superba are a key component of food webs in the maritime West Antarctic Peninsula, and their life history is tied to the seasonal cycles of sea ice and primary production in the region. Previous work has shown a general in-shore migration of krill in winter in this region; however, the very near-shore has not often been sampled as part of these surveys. We investigated distribution, abundance, and size structure of krill in 3 fjordic bays along the peninsula, and in the adjacent Gerlache Strait area using vertically stratified MOCNESS net tows and ADCP acoustic biomass estimates. Krill abundance was high within bays, with net estimated densities exceeding 60 krill m-3, while acoustic estimates were an order of magnitude higher. Krill within bays were larger than krill in the Gerlache Strait. Within bays, krill aggregations were observed near the seafloor during the day with aggregations extending to the sediment interface, and exhibited diel vertical migration higher into the water column at night. We suggest these high winter krill abundances within fjords are indicative of an active seasonal migration by krill in the peninsula region. Potential drivers for such a migration include reduced advective losses and costs, and availability of sediment food resources within fjords. Seasonally near-shore krill may also affect stock and recruitment assessments and may have implications for managing the krill fishery in this area. KEYWORDS: Euphausiid · Abundance · Diel vertical migration · DVM · WAP · Fjord.
Keywords: Sørishavet; biomasse; hydrografi; krill; marin biologi; oseanografi; zooplankton

At-Sea Distribution and Prey Selection of Antarctic Petrels and Commercial Krill Fisheries - Descamps, Sébastien; Tarroux, Arnaud; Cherel, Yves; Delord, Karine; Godø, Olaf Rune; Akiko, Kato; Krafft, Bjørn A; Lorentsen, Svein-Håkon; Ropert-Coudert, Yan; Skaret, Georg; Varpe, Øystein (PloS One, 2016)
Kommersielle fiskerier kan påvirke marine økosystemer og bestander av topp-predatorer som sjøfugl. I Sørishavet foregår et ekstensivt fiske etter Antarktisk krill (Euphausia superba), og dette er antatt å øke. En sammenligning av fordeling og uttak hos fiskeriene og tilsvarende hos topp-predatorene er nødvendig for å forutsi fiskerirelaterte påvirkninger på krillavhengige predatorer. I dette studiet kartla vi næringssøksområdene hos Antarktispetrell (Thalassoica antarctica) som hekker i verdens største koloni (Svarthammaren, Dronning Maud land) over en treårsperiode. Vi fant at det romlige overlappet mellom krillfiskerier og næringssøkende Antarktispetrell generelt var lite. Konkurranse mellom Antarktispetrell og krill-fiskerier er for tiden neglisjerbart, men kan øke hvis fiskeriet etter krill øker.
Keywords: Dronning Maud Land; Sørishavet; fiskeriforvaltning; krill; marinbiologi; ornitologi; økosystem

Gastrointestinal helminths of Adélie penguins (Pygoscelis adeliae) from Antarctica - Diaz, Julia Inés; Fusaro, Bruno; Longarzo, Lucrecia; Coria, Néstor Rubén; Vidal, Virginia; D'Amico, Verónica; Barbosa, Andrés (Polar Research, 2016)
Knowledge about parasitic organisms in Antarctica is scarce and fragmentary. The study reported here adds to the knowledge of gastrointestinal parasites of the Adélie penguin (Pygoscelis adeliae) (Sphenisciformes), from 25 de Mayo/King George Island (South Shetlands), Bahia Esperanza (Hope Bay) and Avian Island (Antarctica). Thirty-five freshly dead specimens (20 chicks and 15 adults) were collected from December 2007 to December 2014 and examined for internal macroparasites. Three adult parasite species were found: one Cestoda, Parorchites zederi, and two Nematoda, Stegophorus macronectes and Tetrameres sp. Immature Tetrabothrius sp. were found in hosts from Avian Island. Helminth communities are known to be related to host feeding behaviours. Low parasite richness observed in Adélie penguins could be related to the stenophagic and pelagic diet of this host species, which feeds almost exclusively on krill. Keywords: Parorchites zederi; Stegophorus macronectes; Tetrameres sp.; parasites; ecosystem health.
Keywords: Antarktis; krill; parasitter; pingviner; plankton; zoologi; økosystemer

Chinstrap and macaroni penguin diet and demography at Nyrøysa, Bouvetøya - Niemandt, Corne; Kovacs, Kit M; Lydersen, Christian; Dyer, Bruce M; Isaksen, Kjell; Hofmeyr, G J Greg; Mehlum, Fridtjof; de Bruyn, P J Nico (Antarctic Science, 2016)
Keywords: Bouvetøya; klimaendringer; krill; pelsseler; pingviner; plankton

Temporal shift in the isotopic niche of female Antarctic fur seals from Bouvetøya - Tarroux, Arnaud; Lowther, Andrew D; Lydersen, Christian; Kovacs, Kit M. (Polar Research, 2016)
The Antarctic fur seal (Arctocephalus gazella) is a key marine predator in the Southern Ocean, a region that has recently started to show changes as a result of global climate change. Here, carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope analyses on whole blood and plasma samples were used to examine the isotopic niche of lactating female Antarctic fur seals. Using recently developed Bayesian approaches to determine changes in isotopic niche, a significant increase in δ 13 C and δ 15 N was found between 1997 and 2015; this change occurred at an average rate of 0.067‰ (δ 13 C) and 0.072‰ (δ 15 N) per year over this period. This suggests that a marked isotopic niche shift has occurred over this period, which very likely corresponds to a shift in diet towards prey at a higher trophic level, such as fish (replacing krill). Although our sampling design prevented us from exploring a seasonal trend in a conclusive manner, our data suggest that concurrent increases in δ 13 C and δ 15 N might occur as the breeding season progresses. At a seasonal scale, an average decrease of −0.7‰ per month (95% confidence interval=[−0.9; −0.6]) in δ 13 C might have occurred, concurrently with an average increase of 1.1‰ per month in δ 15 N. The results of this study constitute the first isotopic assessment for female Antarctic fur seals from Bouvetøya and provide a baseline for the use of this predator species as a sentinel of the marine trophic system in one of the least studied areas within this species' distributional range.
Keywords: Bouvetøya; Sørishavet; klimaendringer; krill; marin biologi; pelsseler; plankton; stabile isotoper; zoologi